Comparative genomic analysis of Lacticaseibacillus paracasei SMN-LBK from koumiss - Wang, Jianghan; Wang, Tong; Li, Yandie; Fan, Zhexin; Lv, Zhuoxia; Liu, Linting; Li, Xu; Li, Baokun (Frontiers in Microbiology, 2022)
Lacticaseibacillus paracasei SMN-LBK, which was isolated in Xinjiang, has been shown to be a probiotic strain and used as the auxiliary starter for dairy fermentation. Comparative genomic analysis was performed to investigate the metabolic preference and ethanol tolerance mechanisms of L. paracasei SMN-LBK. The results of comparative genomics showed that L. paracasei strains had high conservation and genetic diversity. SMN-LBK encoded various genes related to carbohydrate and amino acid metabolism pathways, which endow this strain with good fermentation potential. In addition, 6 CRISPR sequences and 8 cas proteins were found in SMN-LBK, and these could play vital roles in the immune system. Furthermore, a unique cluster of potential secondary metabolism genes related to bacteriocins was detected in the genome of SMN-LBK, and this could be important for the preservation of fermented foods. Multiple genes related to alcohol tolerance were also identified. In conclusion, our study explained the traits that were previously demonstrated for SMN-LBK as phenotypes and provided a theoretical basis for the application of SMN-LBK in the food industry.